Kinetics of carburizing of duplex stainless steel (DSS) by superplastic compression at different strain rates - Ahamad, Nor Wahida; Jauhari, Iswadi; Abdul Azis, Sharidah Azuar; Abd Aziz, Nur Hafizah (Elsevier, 2010)
In this work, superplastic carburizing (SPC) of duplex stainless steel (DSS) under compression mode has been studied. Carburizing was performed at temperatures ranging from 1198-1248 K and strain ranging from 0.1-0.5 under two strain rates (1 x 10(-3) and 1 x 10(-4) s(-1)), A Carburized layer in the range of 17-63 mu m was obtained at the high strain rate whereas at low strain rate the layer was in the range of 50-159 mu m. The activation energy for carburizing varies from 227 kJ mol(-1) at the high strain rate to 183 kJ mol(-1) at the low one. The results have revealed that SPC not only depends on the temperature and strain (time) but also on the strain rate. (C) 2010 Elsevier B.V. All rights reserved.